A unifying model for extrachromosomal circular DNA load in eukaryotic cells. (August 2022) - Arrey, Gerard; Keating, Samuel T.; Regenberg, Birgitte
Abstract: Extrachromosomal circular DNA (eccDNA) with exons and whole genes are common features of eukaryotic cells. Work from especially tumours and the yeast Saccharomyces cerevisiae has revealed that eccDNA can provide large selective advantages and disadvantages. Besides the phenotypic effect due to expression of an eccDNA fragment, eccDNA is different from other mutations in that it is released from 1:1 segregation during cell division. This means that eccDNA can quickly change copy number, pickup secondary mutations and reintegrate into a chromosome to establish substantial genetic variation that could not have evolved via canonical mechanisms. We propose a unifying 5-factor model for conceptualizing the eccDNA load of a eukaryotic cell, emphasizing formation, replication, segregation, selection and elimination. We suggest that the magnitude of these sequential events and their interactions determine the copy number of eccDNA in mitotically dividing cells. We believe that our model will provide a coherent framework for eccDNA research, to understand its biology and the factors that can be manipulated to modulate eccDNA load in eukaryotic cells.